2001
DOI: 10.1097/00003446-200104000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Effects in Dichotic Speech Testing in Elderly Persons

Abstract: Effects of chronologic age in dichotic speech tests in the elderly have been verified. The degree of effect is dependent on test material, way of reporting and focusing condition. The different listening tasks in dichotic tests put different demands on cognitive ability shown by a varying degree of correlations between cognitive function and dichotic test parameters. Also, the results indicate a strong connection between age-related cognitive decline in the elderly and problems to perceive stimuli presented to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
56
1
10

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 25 publications
9
56
1
10
Order By: Relevance
“…The results show a worse performance in all these tests among the elderly. There was a poorer performance in the left side hearing when compared to the right side for the same group, showing the effects of chronological age in dichotic hearing tests 4 . Quintero et al (2002) compared the performance of elderly individuals with normal hearing ones and those with symmetrical sensorineural hearing loss -characteristic of presbycusis, by means of disyllable recognition test in a dichotic task (SSW).…”
Section: Introductionmentioning
confidence: 74%
“…The results show a worse performance in all these tests among the elderly. There was a poorer performance in the left side hearing when compared to the right side for the same group, showing the effects of chronological age in dichotic hearing tests 4 . Quintero et al (2002) compared the performance of elderly individuals with normal hearing ones and those with symmetrical sensorineural hearing loss -characteristic of presbycusis, by means of disyllable recognition test in a dichotic task (SSW).…”
Section: Introductionmentioning
confidence: 74%
“…Similarly, frequency modulation detection was poorer in older than younger subjects and age-related differences were larger at 500 Hz than at 4000 Hz (He et al, 2007). Age-related changes in cognitive functioning, including selective attention, may also negatively affect performance on auditory processing tasks, such as frequency discrimination (Hallgren et al, 2001;Humes, 1996;Humes, 2005;Humes et al, 1991;Humes et al, 2005;Humes et al, 1996;Humes et al, 2006;Humes et al, 1994). Therefore, it is likely that age-related changes in the peripheral, central auditory and cognitive systems contribute to age-related declines in the ability to detect small changes in frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, research has demonstrated that the DLT performance of elderly is decreased compared to younger participants (Alden, Harrison, Snyder, & Everhart, 1997;Bouma & Van der Endt, 1993;Gelfand, Hoffman, Waltzman, & Piper, 1980;Hallgren, Larsby, Lyxell, & Arlinger, 2001;Martin & Cranford, 1991;Strouse, Wilson, & Brush, 2000a). Also, an age-related increase of ear asymmetry has been reported: performance of the LE has been found to decrease stronger than performance of the RE (Jerger, Alford, Lew, Rivera, & Chmiel, 1995;Jerger, Chmiel, Allen, & Wilson, 1994;Strouse et al, 2000a;Strouse, Wilson, & Brush, 2000b).…”
mentioning
confidence: 99%
“…Also, an age-related increase of ear asymmetry has been reported: performance of the LE has been found to decrease stronger than performance of the RE (Jerger, Alford, Lew, Rivera, & Chmiel, 1995;Jerger, Chmiel, Allen, & Wilson, 1994;Strouse et al, 2000a;Strouse, Wilson, & Brush, 2000b). However, this finding is still controversial since some aging studies have failed to find such an effect (Gelfand et al, 1980;Martini et al, 1988) or found that age effects could only be perceived in focussed attention conditions, in particular when attention had to be focussed at the LE (Alden et al, 1997;Bouma & Van der Endt, 1993;Hallgren et al, 2001). Findings of decreased LE performance in elderly suggest that aging differentially affects functional hemispheric asymmetry.…”
mentioning
confidence: 99%